THE EFFECTIVENESS OF YOUTUBE TO IMPROVE STUDENTS' WRITING ABILITY OF DESCRIPTIVE TEXT AT THE GRADE X SMA N 1 ANGKOLA BARAT - Erpina, Sopi (CV. Alfa Pustaka, 2024)
This research aimed to know the effectiveness of using YouTube in improving students' writing ability of Descriptive Text at the grade X of SMA Negeri 1 Angkola Barat. In this research, the researcher used one-group pretest-posttest design, there was not control group. The researcher gave pre-test to student, then, researcher gave the students’ treatment about writing Descriptive Text with video from YouTube. After treatment is given, researcher gives the student post-test. The population in this research were the students of SMA Negeri 1 Angkola Barat. The researcher used random sampling were takes class of X MIPA 2 as the sample of this research. The total of students in this class was 34 students. The score of students' before using YouTube media was 63.52 and it was categorized